Estudo de soluções de buraco negro e buraco de minhoca na teoria de Einstein-Maxwell na presença de campo escalar - Gomes, Tales Augusto Oliveira (2023)
The existence of charged black hole and wormhole solutions in general tensor-scalar theories has been extensively explored in the literature, with such solutions generally only possible for a negative value of the scalar field’s kinetic term. In this work, we classify and analyze charged black hole and wormhole solutions in the Einstein-Maxwell system in the presence of a minimally coupled, massless scalar field. These solutions describe wormholes, naked singularities, and a restricted class of black holes that can have up to two event horizons with infinite surface area and a time-like singularity. These solutions are found in the Einstein frame and can be mapped to the Jordan frame, where the scalar field exhibits a non-minimal coupling to the geometry through a conformal transformation. The classified solutions in this work possess certain specificities compared to the solutions found in the Jordan frame, as discussed in the text.